Origin of high-power drive stability in (Na1/2Bi1/2)TiO3-BaTiO3 based piezoceramics. (1st April 2022) - Slabki, M.; Lalitha, K.V.; Rödel, J.; Koruza, J.
Abstract: Hard-type ferroelectrics are indispensable and increasingly used for numerous high-power piezoelectric resonance applications, ranging from ultrasonic welding and cleaning, to voltage transformers and miniaturized ultrasonic motors in robotics. While the state-of-the-art lead-based ferroelectrics are hitting their operational limits, several new and environmentally-friendly lead-free alternative materials have emerged recently. Particularly compositions of the (Na1/2 Bi1/2 )TiO3 family have demonstrated promising high-power properties and increased depolarization temperatures. However, the underlying mechanisms remain unclear and hamper further development of these materials. Here, we investigate the high-power electromechanical behavior of several (Na1/2 Bi1/2 )TiO3 -based compositions and reveal that these exhibit an inherent intrinsic stability, which is retained at large vibration velocity and broad temperature range also after acceptor doping or composite formation. This results in excellent high-power figures of merit even at vibration velocities beyond 1 m/s, at which the lead-based compositions already fail. Moreover, the critical vibration velocity for fracture was found to be almost two-times higher for (Na1/2 Bi1/2 )TiO3 -based materials, demonstrating their high dynamic fracture strength. The microscopic origin of this behavior was identified using synchrotron radiation, revealing that the strain is dominated by lattice contributions, induced by the emerging mechanical stress. Due to the large coercive stress, the domain wall contributions are in the range of only 3‒5% and, unlike in PZT, remain relatively constant also at higher vibration velocities. The high-power properties and stability are thus determined by the intrinsic loss instead of the usually-dominant extrinsic loss. Graphical abstract: Image, graphical abstract